Multiple Congenital Pancreatic Cysts in a Neonate - Eun Mi Kwon; Jaeho Shin; Ga Won Jeon (Korean Society of Neonatology, 2019)
Congenital pancreatic cysts are rare in newborn babies, and this makes prenatal diagnosis difficult. Diagnosis can be delayed for a few months after birth until the infant presents with an abdominal mass, abdominal distension, or vomiting due to gastric outlet obstruction. Excision of the cyst is the treatment of choice. A congenital pancreatic cyst should be considered if the fetus has an abdominal cyst without a definite origin. A prompt diagnosis is crucial to prevent fatal complications such as cholangitis, pancreatitis, cyst rupture, and peritonitis. We report a case of neonate with multiple congenital pancreatic cysts suspected prenatally to be stomach diverticulum or duplication cysts of the intestine.